How to normatively transform food systems: Propositions of a holistic framework of politics - Abdulai, Abdul-rahim; Bene, Christophe (Cambridge University Press, 2025)
Draws from an extensive literature review on food politics to propose a Framework of Holistic Politics for Food System Transformation. The Framework posits that food systems transformation would be a process/outcome of interrelated political configurations of actions across four processes or stages: 1) Identifying resistance to change in the current regime, 2) Creating and sustaining new momentum, 3) Converting new momentum into sustainable options; -and cross-cutting, 4) Managing trade-offs, reducing incoherence, and prioritization. At each stage, four domains of politics must be considered, including 1) Power, the political economy of actors, knowledge, and evidence; 2) Cultural dynamics, norms, and behavior; 3) Capacity and financial resources; and 4) Technological innovations). To deliver normative transformation, these actions must be carried out in four distinct processes. The Framework underscores the need for normative and goal-oriented processes, the multi-dimensionality of politics, and the normative driving environment in governance food systems transformation.